2013
DOI: 10.1002/ps.3552
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced herbicide metabolism induced by 2,4‐D in herbicide susceptible Lolium rigidum provides protection against diclofop‐methyl

Abstract: Protection against diclofop-methyl provided by 2,4-D pre-treatment in susceptible L. rigidum is associated with higher rates of herbicide metabolism, mirroring that identified in field-evolved, non-target site-based diclofop-methyl resistant populations. 2,4-D may induce higher level expression of herbicide-metabolising genes hence providing protection, and therefore, this 2,4-D induction system can be used, in combination with other genomic approaches, to assist isolating cytochrome P450 and other genes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 18 publications
(43 reference statements)
3
53
0
2
Order By: Relevance
“…For example, a population of prickly lettuce (Lactuca serriola L.) resistant to 2,4-D displayed reduced uptake and translocation compared with a sensitive population, but rates of 2,4-D metabolism not different (Riar et al 2011). It is important to note, however, that these two mechanisms may be physiologically linked; i.e., rapid production of polar metabolites often leads to measurements of decreased translocation since polar metabolites and herbicide conjugates are typically less phloem mobile than parent compounds (Han et al 2013), most likely due to permanent sequestration in the vacuole via phase III transport and detoxification reactions (Devine and Hall 1990;Riechers et al 2010).…”
Section: Number Of Dicot Weed Species and Recentmentioning
confidence: 99%
“…For example, a population of prickly lettuce (Lactuca serriola L.) resistant to 2,4-D displayed reduced uptake and translocation compared with a sensitive population, but rates of 2,4-D metabolism not different (Riar et al 2011). It is important to note, however, that these two mechanisms may be physiologically linked; i.e., rapid production of polar metabolites often leads to measurements of decreased translocation since polar metabolites and herbicide conjugates are typically less phloem mobile than parent compounds (Han et al 2013), most likely due to permanent sequestration in the vacuole via phase III transport and detoxification reactions (Devine and Hall 1990;Riechers et al 2010).…”
Section: Number Of Dicot Weed Species and Recentmentioning
confidence: 99%
“…In contrast, non-target-site resistance (NTSR) is generally considered to be an intricate issue that can be due to enhanced metabolic degration of the herbicides. NTSR is relatively difficult to study than TSR, and NTSR is consindered to be an destructive threating for weed management [16][17][18][19][20][21].…”
Section: Commercialmentioning
confidence: 99%
“…Rigid ryegrass is ranked among the weeds exhibiting most reported cases of herbicide resistance (Heap, 2017) and, currently, resistant populations appear to be highly frequent in surveyed countries, including Australia (Owen et al, 2007) and Spain (Loureiro et al, 2010), among others (Kaundun et al, 2011; Bostamam et al, 2012). First reports of herbicide resistance in this weed species date back to the early 1980s with ACCase- and ALS-inhibiting herbicides being involved (Heap and Knight, 1982). Thereafter, additional cases of resistance across different herbicide modes of action, and also multiple and cross resistance (Heap and Knight, 1986; Fernandez et al, 2016), have been repeatedly reported across 12 countries (Heap, 2017), including resistance to glyphosate.…”
Section: Introductionmentioning
confidence: 99%